Politik Recalling dalam Parlement Riau 2014-2019 - Alexsander Yandra (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
The Interim Replacement between the time (PAW) mechanism of six legislators of Riau at 2014-2016 period through the long mechanism and give rise to polemics both at the elite level and on the society. Strating from the proposal for dismissal by the regional council (DPD) of political parties, approval at the meeting of DPRD, verification of the KPUD of Riau Provinces, the letter proposal that then forwarded to the Minister for issued official announcement of PAW. Delays in the Minister’s decree related determination replacement PAW of the six legislators Riau who participate in 2015 election implication for the vacancy delegation in constituency of the six legislators who resigned. This is administratively highly influential DPRD of Riau in decision making and for the local elections also will impact to reduced their delegations in government. This research used the turnover between the time (PAW) concept and theory of political delegation institutions. This research type is descriptive with qualitative approach, the data collection technique used depth interviews and documentations. The results showed that the mechanism of the six legislators Riau PAW 2014-2019 period after the enactment into regional head candidates in the elections of December 2015 the dynamics of the level of Parliament and political parties Bearers and take quite long. That condition has implications for vacancies in representative institutions (parliament) Riau province where administratively is not full members of Parliament in decisionmaking so that the delay in setting the budget Riau in 2016.